The value of licences for recreational resources use - Michele Moretto; Paolo Rosato (Fondazione Eni Enrico Mattei (FEEM), 2000)
Tools for recreational resources management are topics of great theoretical and practical interest. The most commonly used tool undoubtedly is the licence or permit. The implementation of a system of licences to regulate the use of a natural resource is far from simple as it presupposes the answer to a number of questions. This paper focuses on the point of view of the purchaser and, in particular, models his behaviour when considering the purchase of a licence that authorises him to benefit from a natural resource in accordance with certain rules and procedures. The model assumes that the behaviour can be compared to that of an investor faced with a Call option, i.e. the right (but not the obligation) to make an investment at any time in a given financial unit at a pre-established price. The model was used to study the effect on purchase timing and licence duration of certain factors such as the uncertainty of the benefits and the irreversibility of the purchase. The results show that under uncertainty the consumer tends to delay the purchasing time and, then, to purchase a licence of longer duration than the one that would be purchased considering only the present value deriving from the expected flow of benefits.
Keywords: 330; Option value; irreversibility; natural resources; licences; Lizenz; Optionsgeschäft; Gemeingüter; Freizeit; Theorie